Regional renewable energy resource potential in Pakistan - Salik uddin Ahmed; Abdul Hameed Memon; Amjad Ali Kamboh (Sir Syed University Research Journal of Engineering and Technology, 2020)
Pakistan is currently recovering from a severe, decade-long power crisis which affected the country’s economy and disrupted its’ development. On the other hand, the environmental concerns faced by the South-East Asian region combined with the sustainable development goals to be implemented by Pakistan under the Paris Agreement puts further emphasis on renewable energy deployment. This research investigates the solar, wind and hydro resource potential for power production in different regions of the country. A total of 15 data sources have been reviewed and meta-analytic review techniques is used for analysis. It is found that 13 sources out of 15 (86.67%) have reinforced availability of wind, 12 (80%) have indicated the availability of solar potential and 11 (73.33%) have supported hydro resource potential. With the help of the Spearman correlation test, it is found that wind potential is correlated to RE potential in Sindh and has a correlation coefficient of 0.643 with a significance value of 0.010. In KPK province, the availability of wind and hydro resources are found to be statistically significant. The correlation coefficient for wind potential in KPK is 0.511 with a significance value of 0.052 and the correlation coefficient for hydro potential in KPK is 0.788 having a significance value of 0.001. Unfortunately, statistical significance between any of the investigated RE sources and RE potential in Punjab and Balochistan could not be found. It is recommended that policymakers should design policies and strategies to maximize country’s RE harnessing power and researchers should work towards finding more evidence to support RE deployment in an informed manner.